Mutual Fund Survivorship - Carhart, Mark M.; Carpenter, Jennifer N.; Lynch, Anthony W.; Musto, David K. (Review of Financial Studies, 2002)
This article provides a comprehensive study of survivorship issues using the mutual fund data of Carhart (1997). We demonstrate theoretically that when survival depends on multiperiod performance, the survivorship bias in average performance typically increases with the sample length. This is empirically relevant because evidence suggests a multiyear survival rule for U.S. mutual funds. In the data we find the annual bias increases from 0.07% for 1-year samples to 1% for samples longer than 15 years. We find that survivor conditioning weakens evidence of performance persistence. Finally, we explain how survivor conditioning affects the relation between performance and fund characteristics.